Prestasi Belajar Anak Petani - Maglon Banamtuan; Soleman Baun; Sem Saetban (Institut Agama Kristen Negeri Kupang, 2022)
Aims to describe the attention of farmers to their children at home as an effort to improve their learning achievement at the Boentuka Inpres Elementary School, Batuputih District, South Central Timor Regency. This research uses descriptive research method. Then the research results obtained are Family life experience shows that parents, especially in Boentuka Village, most parents are getting less and less with their children because of their busy schedule to meet the increasingly complex needs of life. This is related to the level of learning achievement achieved by children in school. Efforts to improve children's learning achievement is a complex matter because many parties are involved in it, as well as being a factor that affects the achievement of children's learning achievement levels, especially students who come from farmer family backgrounds who are studying.